Community Perceptions of Integrating Customary Law Norms and Government Regulations in Protecting Legally Vulnerable Marginal Ecosystems - Linda Ikawati; Fifiana Wisnaeni; Sandra Leoni Prakasa Yakub (International Forum of Researchers and Lecturers, 2025)
This study explores the integration of customary law and government regulations in environmental protection, emphasizing the role of community perceptions in shaping effective legal frameworks. Marginal ecosystems, such as coastal areas, urban fringes, and sacred natural sites, often face vulnerability due to fragmented governance systems that fail to coordinate customary practices with formal legal structures. The research investigates how integrating local traditions and state regulations can enhance biodiversity conservation, improve community engagement, and ensure the long term sustainability of environmental management efforts. Findings reveal that when customary laws are formally recognized and incorporated into state regulations, they significantly enhance the legitimacy and effectiveness of conservation policies. Communities in regions like Bali, Indonesia, and Pacific Islands have shown that hybrid legal approaches, which respect traditional ecological knowledge, result in greater participation and trust in conservation activities. However, challenges such as administrative complexity, lack of standardized guidelines, and the need for adequate funding and support for community based governance hinder the full potential of this integration. The study highlights the importance of simplifying legal processes and fostering mutual understanding between customary practices and formal regulations to achieve successful ecosystem protection. This research emphasizes the need for policy reforms that ensure the inclusion of customary law in environmental governance frameworks, ultimately promoting a more inclusive, adaptive, and sustainable approach to managing marginal ecosystems.